The Effect of Coaching Organization Citizenship Behavior Model Grow on Employee Performance - Fitriani, Ana; Ramli, Aburizal Fatwa (International Journal of Multidisciplinary Approach Research and Science, 2024)
The ultimate aims of research are to determine the effectiveness of the GROW model of OCB (Organizational Citizenship Behavior) coaching in improving the performance of PT employees. X. The subjects in this research were employees at PT. X, totaling 16 people from the Marketing Division, were divided into two groups. This research uses an experimental method, with the GROW model OCB coaching intervention in the experimental group. Data analysis used a parametric test with the ANOVA mixed design data analysis technique which looked at the effect of treatment on two groups of subjects. The results of this research were an increase in the performance of the experimental group with a significance score of 0.003 < 0.05. Apart from that, looking at the results of the pretest and posttest comparison, it was 71.6% when compared to the control group. This indicates that there is a significant difference between the group that was given the OCB coaching of the GROW model and the group that was not given the same treatment. In line with the result, companies can therefore improve the performance of their employees by performing the OCB coaching of the GROW model. In addition, it is essential that researchers study the factors that helpinfluence the success of the OCB coaching from different dimensions. Also, researchers should hire professional certified coaches to ensure that the coaching practice shows satisfactory results and is directed following the scientific method.